Chronicles of Qalāwūn and his son al-Ashraf Khalīl
1 online resource.
Keywords: "This volume provides translations of texts on the Mamluk Sultan Qalāwūn (1279-90) and his son al-Malik al-Ashraf (1290-93), which cover the end of the Crusader interlude in the Syrian Levant. Translated from the original Arabic, these chronicles detail the Mamluk perception of the Crusaders, the Mongol menace, how this menace was confronted, and a wealth of materials about the Mediterranean basin in the late thirteenth century. Treaties, battles, sieges and embassies are all revealed in these chronicles, most of which have not been translated previously. The translated texts provide a range of historical records concerning Qalāwūn and al-Ashraf, and include the court perspective of Ibn ʻAbd al-Ẓāhir, the later biography by his nephew Shafīʻ, and the writings of the Mamluk historian Baybars al-Mansūrī"--